Clinical Coding Error with Potential Loss of Hospital Income During Implementation of The Indonesian Case Base Groups Casemix System - Susanto, Anton; Pribadi, Firman (Archives of Business Research, 2023)
The diagnostic code is also the basis for determining the cost of health services. Diagnostic codes that are not qualified will cause losses to the hospital both financially and in policy making. This research method uses qualitative research methods. by using a case study approach (case study). The population which is used are medical record documents of inpatients at dr. Soeratno Gemolong Hospital in Trisemester 4 (October, November, December) in 2019, obtained a sample of 80 documents from a population of 804 documents. The sampling technique used is simple random sampling. The results of the study that the coding accuracy of the Casemix Indonesian Case Base Groups (INA-CBGs) system at Dr. Soeratno Gemolong Hospital Sragen Hospital there are 42 accurate diagnosis codes and 38 inaccurate diagnosis codes, while the inaccuracy of the diagnosis code is caused by the coding error of the main diagnostic code, coding error of the Secondary diagnosis code, coding error Primary and secondary diagnosis code and coding error of the Diagnosis and procedure code. There is a difference between the claim rate from the inaccurate coding and the claim rate from the accurate coding, where the inaccurate coding claim rate generates revenue for the hospital of IDR. 22,816,048 whereas if the claim rate from the correct coding will result in an additional IDR. 41,221,848 for the hospital, so that due to the coding error, the hospital will experience a decrease in income or loss of IDR.18,405,800.